Amphiregulin Regulates Phagocytosis-Induced Cell Death in Monocytes via EGFR and Matrix Metalloproteinases - Platen, Christopher; Dreschers, Stephan; Reiss, Lucy Kathleen; Wappler, Jessica; Orlikowsky, Thorsten W. (Mediators of Inflammation, 2018)
Neonates are highly susceptible to microbial infections which is partially attributable to fundamental phenotypic and functional differences between effector cells of the adult and neonatal immune system. The resolution of the inflammation is essential to return to tissue homeostasis, but given that various neonatal diseases, such as periventricular leukomalacia, necrotizing enterocolitis, or bronchopulmonary dysplasia, are characterized by sustained inflammation, newborns seem predisposed to a dysregulation of the inflammatory response. Targeted apoptosis of effector cells is generally known to control the length and extent of the inflammation, and previous studies have demonstrated that phagocytosis-induced cell death (PICD), a special type of apoptosis in phagocytic immune cells, is less frequently triggered in neonatal monocytes than in adult monocytes. We concluded that a rescue of monocyte PICD could be a potential therapeutic approach to target sustained inflammation in neonates. The EGFR ligand amphiregulin (AREG) is shed in response to bacterial infection and was shown to mediate cellular apoptosis resistance. We hypothesized that AREG might contribute to the reduced PICD of neonatal monocytes by affecting apoptosis signaling. In this study, we have examined a cascade of signaling events involved in extrinsic apoptosis by using a well-established in vitro E. coli infection model in monocytes from human peripheral blood (PBMO) and cord blood (CBMO). We found that CBMO shows remarkably higher pro-AREG surface expression as well as soluble AREG levels in response to infection as compared to PBMO. AREG increases intracellular MMP-2 and MMP-9 levels and induces cleavage of membrane-bound FasL through engagement with the EGF receptor. Our results demonstrate that loss of AREG rescues PICD in CBMO to the level comparable to adult monocytes. These findings identify AREG as a potential target for the prevention of prolonged inflammation in neonates.